Diurnal fluctuations in seawater pCO2 amplify the negative effects of ocean acidification on the biotic performance of the calcifying macroalga Halimeda opuntia - Wei, Zhangliang; Zhang, Yating; Yang, Fangfang; Long, Lijuan (Frontiers in Marine Science, 2022)
Although the adverse effects of increasing atmospheric CO2-induced ocean acidification (OA) on marine calcifying macroalgae have been widely reported, there are limited studies on how daily fluctuations in pCO2 (pH) within shallow ecosystems influence the growth and physiological performance of these calcifiers. Therefore, a 42-day laboratory mimetic experiment to determine how growth, biological performance and related carbon and nitrogen metabolic products of the calcifying macroalga, Halimeda opuntia are generated in response to fluctuating pCO2 under OA conditions (1200 ppmv) was performed. The results of present study showed that the adverse effects of OA were more determined by the adverse influence of elevated acidity (H+) on growth rates, calcification, photosynthesis and the related biotic performance of H. opuntia compared with the positive effects that higher CO2 provided. Moreover, diurnal fluctuations in pCO2 levels [with higher (nearly 8.10) and lower pH (nearly 7.40) values during day and night times, respectively] have amplified these negative influences on H. opuntia. To mitigate elevated pCO2-related stress, higher contents of free amino acids and proline were highly secreted and likely linked to protecting the integrity of algal cellular structures. The above results contribute to increasing our understanding of the biological consequences of pCO2 (pH) variability on calcifying Halimeda species and their physiological plasticity in response to further oceanic pCO2 changes.